2018
DOI: 10.32413/pjph.v8i3.100
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Hand Hygiene Among Health Care Workers in Karachi

Abstract: Background: Hospital acquired infections (HAIs) are one of the most common problems encountered in health care. It is a major cause of concern for hospitals throughout the world. Methods: The study design was cross sectional and data was obtained from health care workers currently employed in hospitals. We selected tertiary care hospitals by convenient sampling technique. Data were analyzed through SPSS version 20. Results: A total of 330 health care workers were included in the study out of which 54.4% (180) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Many tea workers work long hours in the fields, often without proper safety equipment, which can lead to health problems such as respiratory diseases and skin infections (Business & Human Rights Resource Centre, 2022). In addition, many workers are not provided with basic facilities such as clean drinking water and sanitation (Ahmed & Kashem, 2019). There have been some efforts to improve the situation for tea workers in Bangladesh, including efforts to increase wages and improve working conditions (Barkat et al, 2010).…”
Section: F the Present Scenario Of Tea Garden Workers' Exploitation I...mentioning
confidence: 99%
“…Many tea workers work long hours in the fields, often without proper safety equipment, which can lead to health problems such as respiratory diseases and skin infections (Business & Human Rights Resource Centre, 2022). In addition, many workers are not provided with basic facilities such as clean drinking water and sanitation (Ahmed & Kashem, 2019). There have been some efforts to improve the situation for tea workers in Bangladesh, including efforts to increase wages and improve working conditions (Barkat et al, 2010).…”
Section: F the Present Scenario Of Tea Garden Workers' Exploitation I...mentioning
confidence: 99%
“…Previous studies on knowledge of HH among health workers reported varying results ranging from 15.5% to 99.3%. [ 8 9 10 11 12 13 14 15 ] However, little is known about knowledge of HH among eye care workers.…”
Section: Introductionmentioning
confidence: 99%